Functional outcomes of bone marrow aspirate concentrate application in osteoarthritis of the knee - Gursoy, Safa; Akkaya, Mustafa; Simsek, Mehmet Emin; Bozkurt, Murat (International Journal of Research in Medical Sciences, 2019)
Background: Osteoarthritis (OA) of the knee is a very common musculoskeletal disorder. Although total knee replacement is a suitable option in the treatment of severe OA, it has some limitations when performed in the early stage and early age. Bone marrow aspirate concentrate (BMAC), which is rich in mesenchymal stem cells, is promising due to its potentially regenerative and symptomatic effects in many disorders of the musculoskeletal system. This study aims to investigate the efficacy of BMAC in terms of functional recovery in OA of the knee joint. Methods: Total of 52 patients with unilateral symptomatic knee OA but no inflammatory disease, advanced malalignment or instability were enrolled in this study. Bone marrow aspirate was collected from the iliac crest in one session, prepared using a manufactured kit and the patients received intra-articular injections of this BMAC. The mean age of the patients was 59.2±7.4 and the mean follow-up period was 22.1±3.6 months. Functional outcomes of the patients were evaluated using Modified Cincinnati and Tegner Lysholm scoring systems. Results: It was observed that both Lysholm and Cincinnati scores of the patients were statistically significantly higher throughout the follow-up period as compared to the period before the procedure (p=0.0001). There was no statistically significant difference in Lysholm and Cincinnati ratings between gender, side and body mass index groups throughout the follow-up period (p >0.05). It was found that the results of the patients with Kellgren-Lawrence Grade 4 severe joint arthrosis were statistically significantly lower (p <0.05). Conclusions: Considering the functional outcomes of the patients up to two years, it was observed that the application of concentrated bone marrow aspirate provided functional recovery in arthrosis of the knee joint.